Microbial regulation of arsenopyrite oxidation and arsenic transformation in pyrrhotite-mediated interactions - Shuang Zhou; Yusi Qin; Zhiqi Chen; Zhenlei Cai; Yongjie Bu; Weijian Yu; Chenyang Zhang; Keyi Yang; Min Gan; Qingjun Guan (Bioresource Technology, 2027)

Fungal drivers of mycotoxin contamination in wheat: Early warning and plasma-based control - Keyi Zou; Shujuan Chen; Lin Ji; Guoyan Wu; Ke Zhao; Jingxia Fu; Xiumei Yu; Xiaoxue Shan; Likou Zou (Food Research International, 2026)

Pre-existing liver dysfunction modulates di-(2-ethylhexyl) phthalate (DEHP)-associated biological responses through host-microbiome networks - Mingzhu Wu; Shucong Chen; Wencheng Guo; Sijia Gu; Keyi Li; Yumeng Shi; Yu Qian; Yulian Sun; Yarui Liu; Hongkai Zhu (Environmental Pollution, 2026)

Valorizing jackfruit shell into a hydrothermal liquid seed-priming agent for salinity-stressed crops - Tao Zhang; Yanping Zhu; Yongle Yu; Keyi Zhang; Pan Zhao; Xiaomeng Han; Weigang Wang; Shihu Shu; Dandan Ke; Xiuping Zhan; Xiaoshuang Han; Jiping Shi; et al. (Bioresource Technology Reports, 2026)

ΔA146Ply exerts anti-triple-negative breast cancer effects by inducing ferroptosis via regulation of the CYP24A1-mediated calcitriol-vitamin D receptor pathway - Ye Yu; Zhengkun Zhang; Dingxue Wang; Xin Bai; Dan He; Xuxu Ji; Zhaoru Yin; Keyi Xu; Ji Liu; Jiaqiong Zou (Toxicology and Applied Pharmacology, 2026)

Spatiotemporal variability, driving factors, and potential human health risks of fluoride and nitrate in surface water and groundwater of a sandy desert lake basin, Northwest China - Xiangwei Li; Muhan Li; Shen Qu; Keyi Zhang; Yuanzhen Zhao; Ao Gao; Renpu Wang; Dongchao Huo; Zongbao Yue; Bowen Ye; Hongli Ma; Ping Miao; et al. (Journal of Environmental Sciences, 2026)

Toward sustainable postharvest management: A fully bio-based and multifunctional film for fruit preservation - Wenlin Zhou; Keyi Cen; Yutong Yu; Haiyi Zhong; Peiyuan Li (Journal of Environmental Chemical Engineering, 2026)

Multi-isotope coupling models for revealing sulfate source and migration associated with lacustrine groundwater discharge in a large mining area on the Loess Plateau - Zhengguang Zhang; Shen Qu; Xiangyang Liang; Zilong Liao; Yuanzhen Zhao; Keyi Zhang; Chenyu Wang; Fei Gao; Quandong Lian; Ruihong Yu (Process Safety and Environmental Protection, 2026)

Deciphering spatio-seasonal impacts of agricultural irrigation on water quality evolution and surface water-groundwater interaction in a large irrigation district, northwest China - Muhan Li; Keyi Zhang; Wei Bao; Shen Qu; Guanglei Yu; Yansong Bai; Xu Yang; Zeyuan Liu; Hongli Ma; Ping Miao; Fuyang Huang; Ruihong Yu (Journal of Hydrology, 2026)

Contrastive mechanisms of lacustrine groundwater discharge and associated pollutant fluxes into two typical inland lakes in Inner Mongolia, Northwest China - Yuanzhen Zhao; Xiaohui Ren; Shen Qu; Fu Liao; Keyi Zhang; Muhan Li; Juliang Wang; Ruihong Yu (Journal of Environmental Sciences, 2026)

Rapid nucleation and wall-climbing growth of methane hydrate by expanded graphite laminates under static high water-loading conditions - Huizhen Yu; Zixuan Song; Keyi Zhong; Daoyi Chen; Yuanyin Wang; Zihan Yue; Jun Duan; Shuyi Jiang; Mucong Zi (Chemical Engineering Journal, 2026)

A high-performance aqueous redox flow battery with long cyclic stability enabled by a novel Janus membrane self-assembled from polyelectrolytes - Quanhu Sun; Keyi Dong; Zefeng Yan; Tian Lv; Yan Tan; Jiaxin Yang; Yu Wang; Weiyang Tang; Tao Chen (Chemical Engineering Journal, 2025)

Covalency modulated by Fe-F-Fe configuration and oxygen vacancy promotes dual mechanism for oxygen evolution reaction - Bo Feng; Keyi Lv; Ziyong Zhang; Nianwen Song; Ziyang Yan; Yuchao Zhang; Yanfei Wei; Xiaofei Yu; Lanlan Li; Xinghua Zhang; Xiaojing Yang; Zunming Lu; et al. (Chemical Engineering Journal, 2025)

Emergence and genomic characterization of Vibrio parahaemolyticus serotype O10:K4 from seafood-linked diarrheal cases in Zhejiang, China (2016–2023) - Jiewen Huang; Zhen Zhang; Qingtian Li; Jiancai Chen; Lingling Mei; Xiaojuan Qi; Lili Chen; Junyan Zhang; Chao Lv; Min Li; Honghu Chen; Yanjun Zhang; et al. (Food Research International, 2025)

Sweat-amplified dermal transfer and combined toxicity of per- and polyfluoroalkyl substances and organophosphate esters mixtures in children's textiles - Keyi Li; Xiangying Sun; Yu Qian; Wencheng Guo; Yumeng Shi; Mingzhu Wu; Zhipeng Cheng; Hongzhi Zhao; Yarui Liu; Hongkai Zhu (Science of The Total Environment, 2025)

Spatio-seasonal variability of source contributions to water quality in a large irrigation drainage lake basin based on the entropy weighted quality index, positive matrix factorization, and isotopic tracers - Keyi Zhang; Muhan Li; Shen Qu; Yuanzhen Zhao; Limin Duan; Xu Yang; Dingyi Li; Zilong Liao; Ruihong Yu (Environmental Pollution, 2025)

Experimental study on flame characteristics over diesel pool fires under the longitudinal ventilation in curved and inclined tunnels - Xue Wang; Li Yu; Mingnian Wang; Junqi Li; Yuan Liu; Keyi Liu; Zan You (Tunnelling and Underground Space Technology, 2025)

Beyond phthalates: Investigating non-phthalate plasticizers in indoor environments—A nationwide survey from China - Yumeng Shi; Keyi Li; Yu Qian; Wencheng Guo; Yuhao Cao; Zhipeng Cheng; Hongkai Zhu (Journal of Hazardous Materials, 2025)

Dipole-polarized Cu–Ni atomic interfaces for synergistic enhancement and steering of overall nitrogen photofixation - Longjian Li; Ping Zhang; Reyila Tuerhong; Yongchong Yu; Keyi Chai; Lianbiao Zhao; Xiaoping Su; Lijuan Han (Chemical Engineering Journal, 2025)

Spatial variability of lacustrine groundwater discharge and pollutant fluxes in the sandy-land lake group basins: Influence from land use types - Shen Qu; Xiangwei Li; Ao Gao; Yuanzhen Zhao; Keyi Zhang; Yiwei Zhang; Dongchao Huo; Bowen Ye; Zongbao Yue; Renpu Wang; Hongli Ma; Ping Miao; et al. (Journal of Environmental Management, 2025)

Chromosomal structural variation loci HSS1 and HSS6 lead to hybrid sterility in rice - Siqi Cheng; Zhenwei Xie; Hao Yu; Chaolong Wang; Xiaowen Yu; Jian Wang; Hai Zheng; Jiayu Lu; Xiaodong He; Keyi Chen; Junwen Gao; Yang Hu; et al. (Theoretical and Applied Genetics, 2025)

Structural characteization and anti-colorectal cancer activity of a fucogalactan purified from Ganoderma tsugae - Xin Zhang; Shuai Liu; Keyi Wu; Lili Shu; Yu Li; Lanzhou Li; Di Wang (Carbohydrate Polymers, 2025)

Reconstruction of cobalt atoms in ZIF-67 and in-situ growth of carbon nanotubes at low temperature for High-Performance strain sensors - Xiao Li; Tian Lv; Keyi Dong; Jiaxin Yang; Weiyang Tang; Zilin Chen; Yu Duan; Quanhu Sun; Dongmei Zhai; Tao Chen (Chemical Engineering Journal, 2025)

Design of F doped sulfide bifunctional catalyst and investigation on the mechanism transformation of oxygen evolution reaction - Nianwen Song; Keyi Lv; Bo Feng; Ziyong Zhang; Xiangwen Tan; Yanfei Wei; Ziyang Yan; Yuchao Zhang; Xiaofei Yu; Lanlan Li; Xinghua Zhang; Xiaojing Yang; et al. (Chemical Engineering Journal, 2025)

OsPAD1, encoding a non-specific lipid transfer protein, is required for rice pollen aperture formation - Qiming Wang; Yunlu Tian; Keyi Chen; Shanshan Zhu; Yehui Xiong; Chaolong Wang; Xiaowen Yu; Wenting Bai; Hai Zheng; Shimin You; Yang Hu; Dekun Lei; et al. (Plant Molecular Biology, 2025)

Inoculation of thermophilic bacteria from giant panda feces into cattle manure reduces gas emissions and decreases resistance gene prevalence in short-term composting - Jingxia Fu; Shujuan Chen; Yulan Tan; Keyi Zou; Xiumei Yu; Lin Ji; Jianmin Zhang; Xingning Xiao; Wen Wang; Ke Zhao; Likou Zou (Journal of Environmental Management, 2025)

A microphase-separation ionogel electrolyte for highly stretchable all-solid-state supercapacitors - Weiyang Tang; Keyi Dong; Zilin Chen; Yu Duan; Quanhu Sun; Xiao Li; Dongmei Zhai; Tian Lv; Tao Chen (Chemical Engineering Journal, 2024)

Game changer for anaerobic fermentation of paper mulberry: Sucrose-loaded biochar enhancing microbial communities and lactic acid fermentation - Jingwen Cao; Hongzhang Zhou; Xuekai Wang; Yang Wang; Yu Li; Stephen Joseph; Xiaorong Wang; Mengyao Sun; Keyi Zhang; Yanli Lin; Gang Xu; Kuikui Ni; et al. (Bioresource Technology, 2024)

Multi-isotopes (δD, δ18Owater, 87Sr/86Sr, δ34S and δ18Osulfate) as indicators for groundwater salinization genesis and evolution of a large agricultural drainage lake basin in Inner Mongolia, Northwest China - Shen Qu; Yuanzhen Zhao; Keyi Zhang; Juliang Wang; Muhan Li; Xu Yang; Xiaohui Ren; Yanling Hao; Ruihong Yu (Science of The Total Environment, 2024)

6:2 Cl-PFESA, a proposed safe alternative for PFOS, diminishes the gemcitabine effectiveness in the treatment of pancreatic cancer - Jiawei Hong; Keyi Du; Weichen Zhang; Junran Chen; Hangbiao Jin; Yuanchen Chen; Yifan Jiang; Hanxi Yu; Xiaoyu Weng; Shusen Zheng; Jun Yu; Linping Cao (Journal of Hazardous Materials, 2024)

Core-shell nanoconfinement: Nanoreactors for directional electron migration in photothermal-assisted photocatalytic hydrogen production - Yu Shen; Yuxing Shi; Zhouze Chen; Shunhong Zhang; Keyi Chen; Xuefeng Luo; Feng Guo; Guangzhao Wang; Weilong Shi (Chemical Engineering Journal, 2024)

Large-scale surface water-groundwater origins and connectivity in the Ordos Basin, China: Insight from hydrogen and oxygen isotopes - Shen Qu; Chenyu Wang; Nuan Yang; Limin Duan; Ruihong Yu; Keyi Zhang; Muhan Li; Pengfei Sun (Environmental Research, 2023)

A novel hydrogel electrolyte for all-climate high-performance flexible zinc-ion hybrid capacitors within temperature range from −50 to 100 °C - Yu Duan; Tian Lv; Keyi Dong; Feng Zheng; Xiao Li; Yunlong Qi; Zilin Chen; Weiyang Tang; Quanhu Sun; Shaokui Cao; Tao Chen (Chemical Engineering Journal, 2023)

Effect of Dissipation on the Moonpool-Javelin Wave Energy Converter - Dan Yu; Keyi Wang; Yeqing Jin; Fankai Kong; Hailong Chen; Can Yang (Journal of Marine Science and Engineering, 2021)
In this work, the hydrodynamic performance of a novel wave energy converter (WEC) configuration which combines a moonpool platform and a javelin floating buoy, called the moonpool–javelin wave energy converter (MJWEC), was studied by semianalytical, computational fluid dynamics (CFD), and experimental methods. The viscous term is added to the potential flow solver to obtain the hydrodynamic coefficients. The wave force, the added mass, the radiation damping, the wave capture, and the energy efficiency of the configuration were assessed, in the frequency and time domains, by a semianalytical method. The CFD method results and the semianalytical results were compared for the time domain by introducing nonlinear power take-off (PTO) damping; additionally, the viscous dissipation coefficients under potential flow could be confirmed. Finally, a 1:10 scale model was physically tested to validate the numerical model and further prove the feasibility of the proposed system.

Evaluation of All-Sky Assimilation of FY-3C/MWHS-2 on Mei-yu Precipitation Forecasts over the Yangtze-Huaihe River Basin - Yu Li; Keyi Chen; Zhipeng Xian (Advances in Atmospheric Sciences, 2021)

Dihydromyricetin Ameliorates 3NP-induced Behavioral Deficits and Striatal Injury in Rats - Shuhua Mu; Youlan Li; Bingbing Liu; Weiping Wang; Si Chen; Jiajia Wu; Lisi OuYang; Yaxi Zhu; Keyi Li; Mali Zhan; Zongwei Liu; Yu Jia; et al. (Journal of Molecular Neuroscience, 2016)

A novel SNP of the Hesx1 gene in bovine and its associations with average daily gain - Xinsheng Lai; Xianyong Lan; Hong Chen; Xinlei Wang; Keyi Wang; Mou Wang; Hui Yu; Miao Zhao (Molecular Biology Reports, 2009)

The Phosphoenolpyruvate Carboxykinase of Mycobacterium Tuberculosis Induces Strong Cell-Mediated Immune Responses in Mice - Keyi Liu; Xuelian Ba; Jinzhi Yu; Jin Li; Qingkuan Wei; Guangdong Han; Guiping Li; Yong Cui (Molecular and Cellular Biochemistry, 2006)